2021
DOI: 10.1002/berj.3700
|View full text |Cite
|
Sign up to set email alerts
|

Culturally relevant/sustaining pedagogy in a diverse urban classroom: Challenges of pedagogy for Syrian refugee youths and teachers in Turkey

Abstract: This study focused on whether and how teachers implemented the principles of culturally relevant and sustaining pedagogies and the challenges teachers faced while trying to implement these principles with Syrian students in Turkey. The study was built on the four components of pedagogies: academic achievement; cultural competencies; sociopolitical consciousness; and the sustainability of culture. Qualitative data were obtained through interviews and field notes with four teachers who had Syrian students in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Students are likelier to have a good learning attitude when learning is fun and entertaining. Other than that, exciting learning experiences can help students learn better, expand their knowledge, and develop critical thinking skills important for self-development (Kotluk & Aydin, 2021). In remedial education, teachers use real-life examples to solve problems and explain a learning concept differently, aiding students to learn in the remedial classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Students are likelier to have a good learning attitude when learning is fun and entertaining. Other than that, exciting learning experiences can help students learn better, expand their knowledge, and develop critical thinking skills important for self-development (Kotluk & Aydin, 2021). In remedial education, teachers use real-life examples to solve problems and explain a learning concept differently, aiding students to learn in the remedial classroom.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that teachers' practices included both inclusion-oriented and exclusionoriented actions concerning the redistribution, recognition, and representation dimensions of Fraser's social justice framework, which offered a window into inclusive education for imagining new ways of supporting refugee students and their teachers. Kotluk and Aydin (2021) used culturally relevant and sustaining pedagogy as a theoretical lens to examine the challenges teachers faced while trying to implement the principles of this pedagogy. The findings of the study showed that teachers had low expectations of academic achievement from refugee students and designed the teaching-learning process exclusively by considering the perspectives of students from the mainstream culture.…”
Section: The Professional Needs Of Teachers In Turkey In the Context ...mentioning
confidence: 99%
“…Studies on culture and learning suggest that learning should integrate culture into classroom lessons (Günay & Aydin, 2015;Shidiq, 2016). In the case study in Turkey, the teacher did not have sufficient competence or experience to carry out an effective learning process tailored to the needs of Syrian students due to the absence of skills and knowledge (Kotluk & Aydin, 2021). Therefore, these innovations rely on the support of teachers because they were assumed to be their teaching knowledge (Milne et al, 2015).…”
Section: Introductionmentioning
confidence: 99%